PELATIHAN PEMBUATAN MPASI DARI IKAN DI DESA PIJOT KECAMATAN KRUAK KABUPATEN LOMBOK TIMUR - Soraya Gigentika; Dika Arianto; Yuni Mustika; Novandita Esa Rakatama Bassok; Hendry Armadani; Baiq Winda Larasati Hernanda; Ika Handriana; Helfiani Putri; Nirma Nurhaliza; Baiq Aminah Julianfa (Universitas Mataram, 2022)
The problem of stunting is important to solve because it has the potential to disrupt the potential of human resources and is related to the level of health, even child mortality. One area in Indonesia that needs attention in terms of stunting is Pijot Village, which is located in Keruak District, East Lombok Regency, West Nusa Tenggara Province. Efforts made by the University of Mataram in preventing stunting in Pijot Village are involving KKN students to conduct training on making MPASI from fish. The purpose of the training activity is to direct the community to be able to make MPASI from marine fish and provide an understanding to the community of the nutritional content of marine fish. The training on making MPASI from fish applies adult learning methods so that the training is carried out with an active participatory approach, two-way communication, and a combination of theory and practice. The target participants in the training were 22 Posyandu cadres in Pijot Village. The result of the training activities for making MPASI in Pijot Village was that the representatives of Posyandu cadres who attended received increased knowledge or skills in making MPASI. This is evidenced by their success in producing solid food in the form of porridge containing marine fish. In addition, the MPASI from fish produced also has a proper texture and taste for babies aged 6-24 months. No significant obstacles were found in the manufacture of MPASI. Based on the results of the training on making MPASI from fish, it can be concluded that the potential of marine fish in Pijot Village can be processed into MPASI for infants aged 6-24 months because marine fish have very rich nutritional content to meet the nutritional needs of infants so as to prevent stunting in children.